Epstein-Barr Virus Induced Gene-2 Upregulation Identifies a Particular Subtype of Chronic Fatigue Syndrome/Myalgic Encephalomyelitis - Kerr, Jonathan R. (Frontiers in Pediatrics, 2019)
Chronic Fatigue Syndrome / Myalgic Encephalomyelitis (CFS/ME) is a chronic multisystem disease characterised by a variety of symptoms, and exhibits various features of an autoimmune-like disease. Subtypes are well recognised but to date are difficult to identify objectively. The disease may be triggered by infection with a variety of micro-organisms, including Epstein-Barr virus (EBV). A subset of CFS/ME patients exhibit up regulation of EBV virus induced gene 2 (EBI2) mRNA in peripheral blood mononuclear cells (PBMC), and these patients appear to have a more severe disease phenotype and lower levels of EBNA1 IgG. EBI2 is induced by EBV infection and has been found to be upregulated in a variety of autoimmune diseases. EBI2 is a critical gene in immunity and central nervous system function; it is a negative regulator of the innate immune response in monocytes. Its heterogeneous expression in CFS/ME could explain the variable occurrence of a variety of immune and neurological abnormalities which are encountered in patients with CFS/ME. The EBI2 subtype occurred in 38-55% CFS/ME patients in our studies. Further work is required to confirm the role of EBV and of EBI2 and its oxysterol ligands in CFS/ME, and to identify the most practical means to identify patients of the EBI subtype. There are two EBI2 antagonists currently in development, and these may hold promise for the treatment of CFS/ME patients of the EBI subtype.